Structural diversity in metal ion chelation and the structure of uroporphyrinogen III synthase. (August 2002) - Schubert, H. L.; Raux, E.; Matthews, M. A. A.; Phillips, J. D.; Wilson, K. S.; Hill, C. P.; Warren, M. J.
Abstract : All tetrapyrroles are synthesized through a branched pathway, and although each tetrapyrrole receives unique modifications around the ring periphery, they all share the unifying feature of a central metal ion. Each pathway maintains a unique metal ion chelatase, and several tertiary structures have been determined, including those of the protoporphyrin ferrochelatase from both human and Bacillus subtilus, and the cobalt chelatase CbiK. These enzymes exhibit strong structural similarity and appear to function by a similar mechanism. Met8p, from Saccharomyces cerevisiae, catalyses ferrochelation during the synthesis of sirohaem, and the structure reveals a novel chelatase architecture whereby both ferrochelation and NAD + -dependent dehydrogenation take place in a single bifunctional active site. Asp-141 appears to participate in both catalytic reactions. The final common biosynthetic step in tetrapyrrole biosynthesis is the generation of uroporphyrinogen by uroporphyrinogen III synthase, whereby the D ring of hydroxymethylbilane is flipped during ring closure to generate the asymmetrical structure of uroporphyrinogen III. The recently derived structure of uroporphyrinogen III synthase reveals a bi-lobed structure in which the active site lies between the domains.